2005
DOI: 10.1063/1.1913528
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of configurations and third-order nonlinear optical properties of methyl silsesquioxanes

Abstract: Configuration optimizations, excited state properties, and the frequency-dependent third-order nonlinear optical polarizabilities have been investigated on a series of methyl-silsesquioxane (MeT) cages [CH(3)SiO(1.5)](n) (n=4, 6, 8, and 10) using ab initio quantum mechanical methods coupled with the sum-over-states methods. The obtained electronic absorption spectra show a redshift as the cage size increases, and the absorption spectra are assigned as charge transfers from oxygen p type to silicon s type atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Many recent theoretical studies describe HOMO–LUMO interactions in a wide variety of SQ macromonomers. As a prelude to understanding the behavior of the corner-missing cage, we first did calculations for the permethyl cage as shown in Figure . The presence of a spherical LUMO that matches very closely those we have reported previously supports the existence of a similar LUMO in the Ph 7 T 8 R′ cages described above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent theoretical studies describe HOMO–LUMO interactions in a wide variety of SQ macromonomers. As a prelude to understanding the behavior of the corner-missing cage, we first did calculations for the permethyl cage as shown in Figure . The presence of a spherical LUMO that matches very closely those we have reported previously supports the existence of a similar LUMO in the Ph 7 T 8 R′ cages described above.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the electronic properties of the Stil x T 7 -trisiloxy compounds, we calculated the HOMO–LUMO structures of the simplified Me 7 T 7 -trisiloxy analogue per Figure . From our results for Me 7 T 7 -trisiloxy molecule, the HOMO and LUMO energies are −7.37 and 0.91 eV, respectively; a gap of 8.34 eV similar to the theoretical model obtained by Shen et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the enthalpy of formation (Δ r H °) of the proposed dumbbell-like-shaped structure was calculated to be −4.83 eV. Currently, computational studies have suggested that there is a large highest occupied molecular oribital–lowest unoccupied molecular orbital (HOMO–LUMO) gap in silsesquioxane cages. To understand the electronic properties of the Li-T 7 structure, the HOMO and LUMO energies of Li-T 7 were calculated and found to be −7.25 and 0.23 eV, respectively. The HOMO–LUMO gap is around 7.48 eV and is similar to other silsesquioxange cages.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been extensive computational studies carried out on the electronic structure, electronic spectra, optical properties, and reactivity of T 8 octahedral SQs over the past two decades. Phillips et al investigated the absorption excitation energy of functionalized octahedral SQs via time-dependent density functional theory. Using the B3LYP and RSH functional, they found that the excitations are mainly localized on the chromophores, except for vinylsilsesquioxane.…”
Section: Introductionmentioning
confidence: 99%